Public Health Learning Agenda for Systems Change Toolkit: National Pilot Evaluation Results. Issue 2 (9th March 2023) - Welter, Christina; Davis, Sarah; Elnicki, Jill; Kulik, Phoebe K. G.; Lloyd, Laura M.; Tenney, Martha; Todd Barrett, Karla; Rose, Barbara; Walter, Cassidy
ABSTRACT Abstract : Context: There have been multiple calls in the United States for public health workforce development approaches that expand practitioner skill sets to respond to profound inequities and improve population health more effectively. However, most workforce models address individual competencies that instead focus on collective approaches to systems change. Program: In response to this opportunity, the HRSA-funded Regional Public Health Training Centers (PHTCs) and the University of Illinois Chicago Policy, Practice, and Prevention Research Center (P3RC) released Creating a Learning Agenda for Systems Change: A Toolkit for Building an Adaptive Public Health Workforce (the Toolkit) in December 2020. We later supplemented the Toolkit with additional learning activities to launch the Learning Agenda Toolkit Pilot Test (Toolkit Pilot). Implementation: From June to August 2021, 24 diverse teams piloted the Toolkit. Teams completed a multistep process simulating the development of a learning agenda aimed at addressing community health issues and impacting systems change. Evaluation: We conducted an evaluation process to assess the usability and impact of the Toolkit Pilot to inform its improvement and future implementation. An evaluation subcommittee analyzed worksheets completed by the Pilot Teams that are aligned to the Learning Agenda steps and conducted and analyzed 12 key informant interviews using concepts from the Toolkit Pilot Logic Model. Findings and Discussion: Evaluation results suggest that most Pilot Teams found that the Toolkit Pilot offered a step-by-step process toward a clear vision that produced a concrete product on how to address community challenges through learning and systems change. Pilot Teams noted that the Toolkit Pilot provided exposure to and a unique focus on systems thinking; however, prior knowledge of systems thinking and systems change was important. Building readiness for systems change and having more time, resources, and technical assistance would be needed for future versions of the Learning Agenda Toolkit.